(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article studies the scientific and theoretical foundations of attracting foreign investment to the agricultural sector. The definitions expressing the content and essence of investments are analyzed and their specific features are identified. The role of foreign investment in the development of the agricultural sector, in contrast to domestic investment, is revealed. The features, goals, forms and stages of attracting foreign investment to the agricultural sector are highlighted. Factors affecting the investment environment in the agricultural sector are described and classified. Based on the results of the research, practical recommendations are developed for the development of attracting foreign investment to the agricultural sector.